KOMUNIKASI SIMBOLIK MATEN LURIN PADA RITUAL KEMATIAN DI DESA WALANGSAWAH KECAMATAN OMESURI NUSA TENGGARA TIMUR - Florentina Inang; Abbyzar Aggasi (CV. Denasya Smart Publisher, 2025)
This study aims to examine the symbolic meaning contained in the death ritual of Maten Lurin in Walangsawah Village, Omesuri District, Lembata Regency, East Nusa Tenggara. This ritual is a unique tradition performed for individuals who die without adhering to a formal religion, but still believing in the existence of God. Maten Lurin literally means